Keterkaitan Tingkat Kesuburan Perairan Keramba Jaring Apung Dengan Fitoplankton Di Desa Terunyan, Danau Batur, Bali - Nopem, Ifan Martin; Arthana, I Wayan; Dewi, Ayu Putu Wiweka Krisna (Current Trends in Aquatic Science; Vol 3 No 1 (2020), 2020)
This objective of this study is to determine the relationship of the level of water fertility in the waters of cage with phytoplankton in Terunyan Village, Batur lake. Data collected once a week in three months from November 2018 - January 2019. This study used descriptive methods and sampling points were determined using a purposive sampling technique based on the number of cage in the lake which consists of 3 points. Points 1 was the maximum number of cage of ± 500 pieces. Points 2 has a smaller number of cage which was ± 200 pieces. Points 3 was in location of no cage site. The abundance of phytoplankton tend to be less in the point that had more cages and overall the study obtained 14 phytoplankton genera from 4 phyla. The value of phytoplankton Abundance ranges from 4647 -7374 sel/L which is cathegorized in mesotrophic waters. The results of measurement of water quality parameters in a row with the range TSS 5.0 - 6.7 mg/L; Ammonia 0.155 - 0.177 mg/L; Nitrate 0.288 - 0.306 mg/L; Phosphate 0.207 - 0.565 mg/L; pH 7.9 - 8.0; Temperature 26 - 27 0 C, Turbidity 3.049 – 3.410 NTU; DO 6.4 - 6.9 mg/L; Brightness 135.3 - 140.1 cm and TDS 107.5 - 130 mg/L.